Safe and Professional Cyber Counselling: Guidance and Counselling Service Standards in the Digital Age - Arinal Haq Fauziah; Ishlakhatus Sa'idah (ILIN Education Indonesia, 2025)
The digital era necessitates the adaptation of counseling services through cyber counseling innovations that enhance accessibility and flexibility for counselors. However, the absence of explicit standards poses risks such as service misuse, compromised quality, and privacy violations in cyber counseling practices. This study aims to formulate cyber counseling standards using a qualitative approach with a literature review design, analyzing relevant studies from the last five years. The findings highlight key aspects, including counselor competencies, data security, methodological flexibility, and professional ethics. Counselor competencies encompass adherence to counseling values, mastery of fundamental skills, and technological literacy. Data security emphasizes the counselor's ability to uphold confidentiality principles, primarily through the use of high-security platforms. Methodological flexibility involves tailoring counseling services to the specific needs of clients. Additionally, professional ethics serve as essential guidelines for counselors in delivering cyber counseling services. The results of this study are expected to provide a framework for counselors to conduct cyber counseling professionally and effectively while maintaining the essence of face-to-face counseling. The proposed standards will ensure service sustainability and enhance public trust in online counseling.